The Role Of Materialism On Consumer Perceived Values And Online Impulse Buying Behaviour Among Generation Y In Malaysia - Jayapal, Pravina Jayapal (2018)
This study aimed to examine the role of emotional value, social bridging, social bonding and epistemic value on online impulse buying behaviour through materialism. The study incorporates three theories which are the Stimulus-Organism Response Model (SOR), Theory of Consumption Values (TCV) and Social Capital Theory (SCT). A total of three hundred and twelve respondents participated in this study via online survey method. The results revealed that emotional value and epistemic value affect all the dimensions of materialism (success, centrality, happiness).